Effect of Propionic Acid on Diabetes-Induced Impairment of Unfolded Protein Response Signaling and Astrocyte/Microglia Crosstalk in Rat Ventromedial Nucleus of the Hypothalamus - Larysa V. Natrus; Yulia S. Osadchuk; Olha O. Lisakovska; Dmytro O. Labudzinskyi; Yulia G. Klys; Yuri B. Chaikovsky (Neural Plasticity)
Background. The aim was to investigate the influence of propionic acid (PA) on the endoplasmic reticulum (ER), unfolded protein response (UPR) state, and astrocyte/microglia markers in rat ventromedial hypothalamus (VMH) after type 2 diabetes mellitus (T2DM). Methods. Male Wistar rats were divided: (1) control, (2) T2DM, and groups that received the following (14 days, orally): (3) metformin (60 mg/kg), (4) PA (60 mg/kg), and (5) PA+metformin. Western blotting, RT-PCR, transmission electron microscopy, and immunohistochemical staining were performed. Results. We found T2DM-associated enlargement of ER cisterns, while drug administration slightly improved VMH ultrastructural signs of damage. GRP78 level was 2.1-fold lower in T2DM vs. control. Metformin restored GRP78 to control, while PA increased it by 2.56-fold and metformin+PA—by 3.28-fold vs. T2DM. PERK was elevated by 3.61-fold in T2DM, after metformin—by 4.98-fold, PA—5.64-fold, and metformin+PA—3.01-fold vs. control. A 2.45-fold increase in ATF6 was observed in T2DM. Metformin decreased ATF6 content vs. T2DM. Interestingly, PA exerted a more pronounced lowering effect on ATF6, while combined treatment restored ATF6 to control. IRE1 increased in T2DM (2.4-fold), metformin (1.99-fold), and PA (1.45-fold) groups vs. control, while metformin+PA fully normalized its content. The Iba1 level was upregulated in T2DM (5.44-fold) and metformin groups (6.88-fold). Despite PA treatment leading to a further 8.9-fold Iba1 elevation, PA+metformin caused the Iba1 decline vs. metformin and PA treatment. GFAP level did not change in T2DM but rose in metformin and PA groups vs. control. PA+metformin administration diminished GFAP vs. PA. T2DM-induced changes were associated with dramatically decreased ZO-1 levels, while PA treatment increased it almost to control values. Conclusions. T2DM-induced UPR imbalance, activation of microglia, and impairments in cell integrity may trigger VMH dysfunction. Drug administration slightly improved ultrastructural changes in VMH, normalized UPR, and caused an astrocyte activation. PA and metformin exerted beneficial effects for counteracting diabetes-induced ER stress in VMH.